2012
DOI: 10.1186/gm370
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected findings of variability in microRNAs suggest roles in human genetics

Abstract: Short RNA molecules were considered to be junk for decades, but in recent years they have been shown to have important functional roles. MicroRNAs (miRNAs) in particular have attracted much attention. They have been assumed to be highly conserved in humans and other species; however, a recent study published in Genome Medicine reveals an unexpected level of variability in human miRNAs, including variations within the seed region. This challenges the current view of miRNAs, and may explain previous reports of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
2
1
0
Order By: Relevance
“…Other studies found that miRNA precursors with increased expression were mir-22-1, −424, −301, −100, −376a, −125b-1, −021, −016-1, −181a, c, −092-1, −092-1, −212, −107, −024-l, 2, 1et-7f-1, 1et-7d, mir-345, −142-p, −139 (14,29). These results were similar to those of Volinia (30). Volinia (30) and Zhou et al (31) used endpoint immuno PCR to detect the expression of mir-196a in normal pancreatic cells, pancreatic duct epithelial neoplasms (PanIN, precancerous) cells and pancreatic cancer cells.…”
Section: Mirnasupporting
confidence: 91%
See 2 more Smart Citations
“…Other studies found that miRNA precursors with increased expression were mir-22-1, −424, −301, −100, −376a, −125b-1, −021, −016-1, −181a, c, −092-1, −092-1, −212, −107, −024-l, 2, 1et-7f-1, 1et-7d, mir-345, −142-p, −139 (14,29). These results were similar to those of Volinia (30). Volinia (30) and Zhou et al (31) used endpoint immuno PCR to detect the expression of mir-196a in normal pancreatic cells, pancreatic duct epithelial neoplasms (PanIN, precancerous) cells and pancreatic cancer cells.…”
Section: Mirnasupporting
confidence: 91%
“…These results were similar to those of Volinia (30). Volinia (30) and Zhou et al (31) used endpoint immuno PCR to detect the expression of mir-196a in normal pancreatic cells, pancreatic duct epithelial neoplasms (PanIN, precancerous) cells and pancreatic cancer cells. It was found that, in normal pancreatic cells, mir-196a expression was not present; however, PanIN and all tumor cells showed positive expression of miR-196a, suggesting that mir-196a might indicate the carcinogenic transformation process of pancreatic cells.…”
Section: Mirnasupporting
confidence: 91%
See 1 more Smart Citation